Analisis Pengaruh Return On Equity Dan Net Profit Margin Terhadap Return Saham - Berliana Ananda Kutaningtyas; Nurul Fitri Azzahra; Siska Nur Agustin; Ujang Suherman (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The profitability ratio is used as a benchmark in determining stock returns, because the profitability ratio is a ratio that measures how efficiently a company uses its assets and manages its operations. The higher the profit generated, the higher the stock return that investors will get. Included in this ratio are ROE (Return on Equity) and NPM (Net Profit Margin). The design of this research is a Literature Review or literature review. ROE is often referred to as profitability of own capital. This amount is obtained by dividing net profit after tax by total capital. A high ROE number shows the industry's ability to generate profits for shareholders. On the other hand, a high level of profitability will cause less external funds to be used. Companies with high profitability will have large internal funds. An increase in ROE increases the company's sales value, which has an impact on share prices. These two factors have a positive influence on stock returns, which means companies with high ROE and net profit margin tend to have higher stock returns. Therefore, investors can consider ROE and net profit margin as indicators of company performance that can influence stock returns when choosing investments.